Characteristics Analysis of Double-Sided Permanent Magnet Linear Synchronous Motor with Three-Phase Toroidal Windings - Chai , Xiaobao; Si, Jikai; Hu, Yihua; Li, Yingsheng; Wang, Dongshu (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper proposes three-phase 120° phase belt toroidal windings (120°-TW) and are applied in a double-sided permanent magnet linear synchronous motor (DSPMLSM), in which the incoming ends of all coils are on the same side and have the same incoming direction. First, the structure of the proposed motor is introduced and its operation principle is analyzed by describing the variation in the armature magnet field versus time. Second, based on the similar volume, magnetic load and electrical load, the initial parameters of the DSPMLSM with different winding arrangements are presented. Then, the finite-element models (FEMs) of the DSPMLSM with 120°-TW (120°-TWDSPMLSM) and traditional toroidal windings (TTW) are established to analyze the distribution of magnetic field, back electromotive force (back-EMF), detent force, thrust, efficiency and so on. Besides, the primary optimization of the detent force is designed. Finally, the results show that the thrust density and efficiency of the 120°-TWDSPMLSM is higher than that of DSPMLSM with TTW (TTWDSPMLSM).